A super Asian dust storm over the East and South China Seas: disproportionate dust deposition - Hsu, Shih-Chieh; Tsai, Fujung; Lin, Fei-Jan; Chen, Wei-Nai; Shiah, Fuh-Kwo; Huang, Jr-Chuan; Chan, Chuen-Yu; Chen, Chung-Chi; Liu, Tsun-Hsien; Chen, Hung-Yu; Tseng, Chun-Mao; Hung, Gwo-Wei; et al. (American Geophysical Union, 2013)
A super Asian dust (SAD) storm that originated from North China has affected East Asia since 20 March 2010. The tempo-spatial and size distributions of aerosol Al, a tracer of wind-blown dust, were measured on a regional aerosol network in March 2010. Two dust events were recorded: the SAD and a relatively moderate AD event. The SAD clouds raised Al concentrations to ~50 µg/m3 on 21 and 22 March over the East China Sea (ECS) and occupied there for ~5 days. The SAD plume also stretched toward the South China Sea (SCS) on 21 March however, it caused a maximum Al concentration of ~8.5 µg/m3 only, much lower than that observed in the ECS. In comparison, a weaker dust plume on 16 March caused Al maximum of ~4 µg/m3 over the ECS, and comparably, ~3 µg/m3 in the SCS. Dry dust deposition was measured during the peak phase of the SAD at 178 mg/m2/d, which corresponded to dry deposition velocities of 0.2–0.6 cm/s only, much lower than the commonly adopted one (1–2 cm/s). The corresponding increase in dust deposition by the SAD was up to a factor of ~12, which was, however, considerably disproportionate to the increase in dust concentration (i.e., the factor of over 100). In certain cases, synoptic atmospheric conditions appear to be more important in regulating dust contribution to the SCS than the strength of AD storms.